Influences of various pricing points: An experimental study of plastic bags in Johannesburg, South Africa - Johane Dikgang; Zafeer Ravat; Jugal Mahabir (Journal of Applied Economics, 2022)
Policymakers have little experience regarding designing the right levels of pricing for plastic bags. The ineffectiveness of charging for bags, in countries such as South Africa, makes it imperative that we map the demand curve. Getting the charge "right" depends on the size of the externality. Charging for bags is therefore an effective intervention to encourage consumers to carry their own bags to the stores. We employ a contingent behaviour (CB) dataset necessary to estimate the charge level that is likely to lead to a reduction in bag use over time. The results of the random effects Tobit model suggest that the current charge of US0.03 was found to be too low, and highly inelastic. A charge of US0.50 has potential to reduce unnecessary plastic use and is still lower than the price of alternatives; therefore, there is no danger of consumers shifting to alternatives that may cause more harm.
Keywords: 330; Contingent behaviour; levy; plastic bag; price